Pandangan Hukum Islam Tentang Hak Waris Anak Dalam Kandungan - Nur Ma’rifah.A; Andi Satrianingsih; A. Asdar (Jurnal Pendidikan Agama Islam, 2025)
This study was conducted with the following objectives: (1) to examine the Islamic legal perspective on the inheritance rights of a fetus (an unborn child), and (2) to identify the methods of distributing inheritance rights to a child in the womb. This research employs a qualitative method through library research, supported by a normative juridical approach—an approach that focuses on legal aspects and places legal norms at the center of analysis. The data presented in this study are derived from the Qur’an, hadith collections, works of fiqh, academic journals, and other relevant literature. These materials were collected and analyzed to produce an accurate description of the legal provisions related to the Islamic legal perspective on the inheritance rights of a child in the womb. The findings of this study indicate that: (1) there are two cumulative requirements that must be fulfilled for a child in the womb to have an inheritance relationship with the deceased (the heir) and thus be entitled to receive their share, namely: the confirmed existence of the fetus in the mother’s womb at the time of the heir’s death, and the child being born alive; (2) in the distribution of inheritance to a fetus according to Islamic law, there are two possible methods: postponing the distribution until the child is born, or distributing the inheritance while the child is still in the womb.